Elevated serum uric acid is associated with the risk of advanced staging and vascular involvement in patients with hepatoblastoma: a 14-year retrospective study - Zhou, Yunlan; Li, Jinning; Ma, Yanhui; Tang, Mengjie; Yuan, Xiaojun; Shen, Lisong (Frontiers in Oncology, 2023)
Background: Uric acid is the end product of the purine metabolism pathway, and has been linked to cancer risks and prognosis, but its relationship with hepatoblastoma (HB) remains unclear. This study aims to investigate the association between serum uric acid (SUA) and the advanced tumor staging and unfavorable extra-parenchymal tumor characteristics in patients with HB. Methods: This study enrolled pediatric patients from Xinhua Hospital between 2007 to 2021. A total of 101 participants with newly diagnosed HB were recruited in the study. PRETreatment EXTent of disease (PRETEXT) / PostTreatment Extent of disease (POSTTEXT) staging were evaluated at diagnosis and following neoadjuvant chemotherapy (NAC). Adjusted smoothing spline plots, subgroup analysis and multivariate logistic regression analysis were conducted to estimate the association of different levels of SUA with the advanced tumor staging and present annotation factors. Results: In accordance with SUA tertiles, those patients with higher pretreatment SUA levels showed increased percentages of PRETEXT group IV, vessel involvement and multifocality of tumors. After fully adjustment with the confounding factors, SUA was positively associated with advanced PRETEXT stage IV (OR: 1.72, 95%CI 1.15-2.57, p=0.0080), as well as vascular invasion (OR: 1.29, 95%CI 1.01-1.64, p=0.0396). Compared with the lowest SUA concentration tertile, the highest tertile were independently associated with vessel involvement of tumor in all of the adjusted models. Following NAC, SUA levels were significantly reduced in response to the downstaging of tumors. SUA remained positively associated with advanced POSTTEXT staging and vessel involvement in adjusted models. Patients with highest tertile of posttreatment SUA showed worse 5-year EFS and OS. Conclusion: Elevated SUA were associated with an increased occurrence of advanced PRETEXT/ POSTTEXT staging and unfavorable vessel involvement at diagnosis and following NAC in patients with HB. High posttreatment SUA reflected poor tumor responses to NAC. This study linked SUA, a non-invasive laboratory test, with tumor staging and risk prediction for HB.